Tribological behavior of 316L stainless steel reinforced with CuCoBe + diamond composites by laser sintering and hot pressing: a comparative statistical study - Cunha, Ângela Sofia Varela (2020)
The aim of this work was to perform a statistical analysis in order to assess how the tribological properties of a laser textured 316L stainless steel reinforced with CuCoBe - diamond composites are affected by diamond particles size, type of technology (laser sintering and hot pressing) and time of tribological test. The analysis started with the description of all response variables. Then, by using IBM® SPSS software, the Friedman’s test was used to compare how the coefficient of friction varied among samples in five-time points. From this test, results showed that there was no statistically significant difference in the coefficient of friction mean values over the selected time points. Then, the two-samples Kolmogorov-Smirnov (K-S) test was used to test the effect of the diamond particles size and the type of technology on the mean of the coefficient of friction over time. The results showed that, for both sintering techniques, the size of the diamond particles significantly affected the values of the coefficient of friction, whereas no statistical differences were found between the tested sintering techniques. Also, the two-way ANOVA test was used to evaluate how these factors influence the specific wear rate, which conducted to the same conclusions drawn for the previous test. The main conclusion was that the coefficient of friction and the specific wear rate were statistically affected by the diamond particles size, but not by the sintering techniques used in this work.